NARRATIVE REVIEW: METHODS FOR MONITORING AND ANALYZING WARFARIN IN BLOOD - Yuniarti, Windi Astika; Susilo, Rinto; Sundhani, Elza (Jurnal Farmasi Sains dan Praktis, 2026)
Warfarin is an oral anticoagulant with a narrow therapeutic index and high interindividual variability in pharmacokinetic and pharmacodynamic responses, requiring careful therapeutic monitoring to maintain efficacy and minimize adverse events. In clinical practice, anticoagulation monitoring is generally performed using the International Normalized Ratio (INR); however, INR values may be influenced by various factors such as drug interactions, dietary vitamin K intake, patient adherence, and genetic polymorphisms, potentially limiting its accuracy as a sole monitoring parameter. Therefore, direct measurement of plasma warfarin concentrations has gained attention as an additional approach to optimize individualized therapy. This narrative review aimed to evaluate and compare analytical methods used for monitoring and analyzing warfarin levels in blood, particularly high-performance liquid chromatography (HPLC) and liquid chromatography–tandem mass spectrometry (LC–MS/MS). Literature sources were obtained from PubMed and selected based on relevance to analytical methods for warfarin quantification published within the last ten years. The reviewed studies demonstrated that LC–MS/MS provides superior sensitivity, specificity, and low detection limits for accurate quantification of warfarin and its metabolites, while HPLC methods remain reliable, accurate, and applicable in routine clinical laboratories with more limited instrumentation. Several studies also reported that plasma warfarin concentration, especially the unbound fraction, may better reflect anticoagulant activity and bleeding risk in certain patient populations compared with INR alone. In conclusion, chromatographic methods are valuable tools for therapeutic drug monitoring of warfarin and may improve individualized anticoagulant therapy when combined with conventional INR monitoring.